CULTURAL ADJUSTMENTS IN TRANSLATION OF ENGLISH TO INDONESIAN IN NATIONAL GEOGRAPHIC - Yoharwan Dwi Sudarto; Suhartono Suhartono; Mintowati Mintowati (Universitas Negeri Makassar, 2020)
This study describes the technique in translation which is used in the TV show National Geographic. The technique is from Molina and Albir. This research is aiming to discover the culture adaptation, addition and reduction, literal translation, linguistic adaptation in the subtitle from source language to target language. This research is started by choosing the show, transcripting the English, and rewriting the subtitle on the screen. After that, the data is analyzed from the culture adaptation point of view in translating English into Indonesian. The result of this research showed that there is culture adaptation in translating English as source language into Indonesian as target language. First point is the cultural adaptation which adapts with the habit of communicating in target language. This adaptation needs comprehension of the habit of communication in both language. Second, it is addition and reduction which make the result of translation more informative, short, and logical. Next thing is the literal translation which translates the source language literally. Then the linguistic adaptation which adapts the grammar of source language to target language. The data received had been researched to be analyzed in the translation technique.